Sucrose and molasses in simple or complex diets for nursery pigs - I Mavromlichalis; Robert H Hines; B W Senne; S P Sorrell; H Cao; Joe D Hancock; Joel M DeRouchey (Kansas Agricultural Experiment Station Research Reports, 1998)
Three experiments were conducted to determine the effects of replacing lactose with sucrose and molasses in simple and complex diets for nursery pigs. In general, complex diets supported greater growth performance than simple diets, and added lactose and sucrose gave greater efficiency of growth than diets without added sugars. Comparisons among sugar sources indicated that lactose, sucrose, and molasses were utilized equally well by weanling pigs.; Swine Day, Manhattan, KS, November 19, 1998
Keywords: Swine day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 819; Swine; Lactose; Surcrose; Molasses; Nursery pigs